2018
DOI: 10.1108/raf-04-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

The long-run performance of US firms pursuing IPOs in foreign markets

Abstract: Purpose The purpose of this paper is to investigate the long-run performance of a unique set of US domiciled firms that have bypassed the US capital markets in pursuit of their initial public offering (IPO) overseas. Additionally, this paper then tests the popular underwriter prestige impact and the window of opportunity hypothesis on this unique subset of IPOs. Design/methodology/approach Using a sample of foreign and purely domestic IPOs made by US firms from 2000 to 2011, this study investigates the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Goergen, Khurshed and Mudambi (2007) did not find any statistically significant relation between the age of the issuing company and its performance in the long run. The same results were obtained by Killins and Egly (2018). Que and Zhang (2019) obtained mixed results when calculating the relation between age and underperformance as depending on the method used to calculate rates of return, their results showed either an insignificant or positive and statistically significant relation.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Goergen, Khurshed and Mudambi (2007) did not find any statistically significant relation between the age of the issuing company and its performance in the long run. The same results were obtained by Killins and Egly (2018). Que and Zhang (2019) obtained mixed results when calculating the relation between age and underperformance as depending on the method used to calculate rates of return, their results showed either an insignificant or positive and statistically significant relation.…”
Section: Introductionsupporting
confidence: 70%
“…Belghitar and Dixon (2012) showed that VC-backed and unbacked IPOs underperform benchmark portfolio, but their findings are statistically insignificant. Killins and Egly (2018), as well as Goergen et al (2007), found that issuers backed by VCs experience poorer returns in the long run.…”
Section: Introductionmentioning
confidence: 97%
“…Extensive research tests the short-run and long-run performance of IPOs (Loughran and Ritter, 1995;Jenkinson and Jones, 2009;Ang and Boyer, 2009;Lewellyn and Bao, 2014). Previous research in the US markets (Brav et al, 2000), UK (Levis, 1993;Goergen et al, 2007) and other international markets (Lee et al, 1996;Kooli and Suret, 2004;Killins and Egly, 2018) find similar findings of IPO underperformance. Evidence of underperformance is prevalent in the emerging economies as well (Kiymaz, 2000;Hensler et al, 2000;Smith and Chun, 2003;Naifar, 2011;Otchere and Vong, 2016).…”
Section: Related Literaturementioning
confidence: 87%